THE EFFECT OF USING INQUIRY BASED LEARNING STRATEGY ON STUDENTS SPEAKING ABILITY ( A Case Study at SMAN 7 Bengkulu Selatan) - Yogi Irawan; Syahrial Syahrial; Dedi Sofyan (JOALL (Journal of Applied Linguistics and Literature), 2018)
This research is aimed at finding out to what extent IBL strategy can affect students speaking ability and to find out the significant of IBL strategy on students speaking ability. The populations of this study were all students in second grade at SMAN 7 Bengkulu. The samples of this study were 30 students on one class of second grade at SMAN 7 Bengkulu Selatan. This study used quasi-experimental study with one group design in order to test hypotheses. The study was conducted by pretest, the treatment in three meetings by using IBL strategy and posttest to the students. The instruments of this study were pretest and posttest. The result of this research showed that there were increasing scores of students speaking ability from 40,27 to 51,33, the increasing scores covered in; vocabulary aspect (13,54), grammar aspect (10,67), fluency aspect (7,33), and pronunciation aspect (12,67). The conclusions of the study were: firstly, IBL strategy affected students speaking ability with average increasing score of 11,05 covering the four aspects (vocabulary, gramar, fluency and pronunciation) of speaking. Secondly, IBL strategy affected sufficiently significant ( 0,05) on students speaking ability. This current study contributes to give the teachers an additional strategy on the effective strategy for teaching of speaking.